Diversity of the Paedomorphic Snail-Eating Click-Beetle Genus Malacogaster Bassi, 1834 (Elateridae: Agrypninae: Drilini) in the Mediterranean - Hoffmannova, Johana; Kundrata, Robin (Biology, 2022)
The soft-bodied click-beetle genus Malacogaster Bassi, 1834 from the Mediterranean region has never been taxonomically revised to date. Information on its morphology, intra- and interspecific variability, systematics and distribution is fragmented and most species have not been properly studied since their description. Therefore, in this study we summarize all available information on the genus Malacogaster. Altogether, we recognize 10 valid species from the area including the Canary Islands, Iberian Peninsula, Balearic Islands, northern coast of Africa, Sardinia, and Sicily. Malacogaster ruficollis Dodero, 1925, stat. nov., which was originally described as a variety of M. bassii Lucas, 1870 and later synonymized with it, is considered a separate species. Malacogaster parallelocollis Reitter, 1894, syn. nov. and M. olcesei var. reductus Pic, 1951, syn. nov. are synonymized with M. maculiventris Reitter, 1894. Malacogaster notativentris Pic, 1951, syn. nov. and M. olcesei Pic, 1951, syn. nov. are synonymized with M. passerinii Bassi, 1834. Lectotypes are designated for M. maculiventris Reitter, 1894, M. nigripes heydeni Reitter, 1894, M. parallelocollis Reitter, 1894, M. thoracica Redtenbacher, 1858, M. olcesei Pic, 1951, and M. rubripes Peyerimhoff, 1949 to fix their identity.
Keywords: Cantharoidea; Africa; systematics; Elateroidea; Italy; Spain; identification key; neoteny; Coleoptera